Pyrolysis of holm-oak wood: influence of temperature and particle size - Figueiredo, J. L.; Valenzuela, C.; Bernalte, A.; Encinar, J. M. (Fuel, 1989)
The pyrolysis of holm-oak wood sawdust was studied to determine the characteristics of the charcoal and the nature and amounts of gases produced. The temperature was varied from 300 to 900 °C and the wood particle size from 0.40 to 2 mm diameter. The fixed carbon content of the charcoal increased with temperature up to 700 °C, and then remained essentially constant. The gases produced were mainly CO, CO2, H2 and CH4. The rate constants and activation energies for the production of each gas were calculated assuming first order kinetics. The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is ≈ 600 °C.
Keywords: charcoal; Particle Size; pyrolysis